The contribution of cardiovascular mortality to long term outcomes in a relatively young demographic following acute pulmonary embolism: A validation study. (15th November 2015) - Hee, L.; Ng, A.C.C.; Huang, J.; Chow, V.; Mussap, C.; Kritharides, L.; Thomas, L.
Abstract: Background: Long-term studies following acute pulmonary embolism (PE) remain limited in the current era. A recent study from our collaborative group, in a contemporary adult population, showed substantially increased cardiovascular mortality following PE. We sought to evaluate the contribution of cardiovascular mortality to long-term outcomes in a different demographic that comprised of a significantly younger PE cohort. Methods and results: Demographic and clinical characteristics were retrospectively collected for this cohort, and similar methods and outcome measures were applied as detailed in the original study. We compared a population from a different metropolitan area (LH: Liverpool Hospital) to that from the original study (CRGH: Concord Hospital) over a similar time period. A total of 815 patients comprised this cohort with mean 5.3 ± 3.8 year follow-up. There were similar demographics between the two cohorts, though the mean age was significantly younger in LH group (60 vs 68 years, p < 0.001). Prior history of cardiovascular disease in the LH group was half of that present in the CRGH cohort. The overall mortality was 7.4% per patient-year. Patients with underlying cardiovascular disease when presenting with an acute PE had a 2.3-fold increased risk of death during follow-up compared to those without. Multivariate analysis showed that older age, male gender, malignancy, diabetes, cardiovascular disease and chronic pulmonary disease were independent predictors of post-discharge mortality. Conclusions: Despite our cohort being significantly younger with a lower incidence of pre-existing cardiovascular disease, cardiovascular disease was still a significant contributor to long-term outcomes and an important predictor of mortality following acute PE.